A Changing Policy Toward the British Public Sector and its Impact on Service Delivery (CPP RPS 38/2013) - Antonowicz, Dominik (Center for Public Policy Research Papers Series, 2013)
Since the 1980s public service in the UK has undergone a long process of far-reaching and complex changes. It has been a high profile issue for politicians, media and citizens (attracting their attention). There are three major sets of principles which constitute the government’s policies toward public service in modern British politics: the post-war settlement underpinned by social economics, the New Right based on a neo-liberal set of values and the New Labour approach which aimed to combine social values with market mechanisms. Each of them has had a great impact on the development of public service and has contributed, at least to some extent, a valuable input. However, despite Government continues commitment to improvements in both efficiency and effectiveness, the firm perception that public service is under-performing in certain areas exists in society, undermining the recent attempts to reform the system. Despite the fact that general discussion about public service in the UK is limited to the traditional choice between private sector providers and the status quo ante, there are many public service organisations which have managed to develop a variety of innovative approaches to their services, retaining their distinctive values whilst increasing their effectiveness and responsiveness to the needs of citizens. The paper is based on detail studies and extensive research conducted in 2003/2003 in the UK and in general has three major aims. The first one is to examine the governmental policies toward the public sector in the UK which has been developed between the postwar settlement and the present time, paying special attention to political and economic values which underpinned them. The second aim is to analyze and illustrate the impact of the political principles of New Labour on the development of innovative models of public service which have been recently flourished across the UK. The final aim is, using case studies, to define the nature of innovations by presenting their unique features in a wider political and organizational context and investigating what precisely makes the difference.
Keywords: Public service; the New Left; Thatchersim; New Public Management; the Third Way